Intellectual disability and assistive technologies in the context of basic education (Research, Society and Development, 2022)
Intellectual disability is part of the developmental disorder group because it manifests before the individual's eighteen years of age. The classroom teacher must be aware of the signs that his students may present so that he can adapt his planning in order to include this student in an affective and effective way. Therefore, this article aimed to reflect on the importance of assistive technologies in basic education in the context of intellectual disability. The method of data collection and development of the study is based on an integrative literature review. With regard to its main results, the study revealed that it should be taken into account that each student has a different way of learning certain content, however the student who has an intellectual disability has a more pronounced difficulty in carrying out the proposed activities. And to help the student with ID, the teacher can and should make use of the technology resources available to demonstrate the use of that content in their daily lives.